Joseph Green, producent polskich filmów jidyszowych - Włodek, Roman (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2019)
Włodek Roman, Joseph Green, producent polskich filmów jidyszowych [Joseph Green, producer of Polish Yiddish-language films]. „Images” vol. XXVI, no 35. Poznań 2019. Adam Mickiewicz University Press. Pp. 77–101. ISSN 1731-450X. DOI 10.14746/i.2019.35.04. Joseph Green (1900–1996), born Josef Chaim Grinberg in Łódź, was one of the most important producers of films in Yiddish. At the beginning of the sound era in the United States, he worked on dubbing in Yiddish for Jewish films, including Joseph in the Land of Egypt. He received a copy of the film as a royalty, which he then used with great success. The money helped him produce four Jewish films in Poland between 1936 and 1938: Yiddle with His Fiddle, The Jester, Little Mother and A Letter to Mother. Green left Poland in the spring of 1939. When the world of Shtetls – evoked by him – disappeared as a result of the Second World War, he ceased making films.